Kittrick and Wheelock syndrome Mucous-secreting adenoma of the colon - Machín, Mariela; Montero, Hugo; Derboghosian, Alejandro; Colet, Andrés; Rondán, Mariela (Cirugía del Uruguay, 2002)
A patient had a rare clinical case of McKittrick and Wheelock syndrome consisting of a hypersecreting villiferous adenoma accompanied by dehydration, dysiony and renal insufficiency.